2020
DOI: 10.1042/bsr20194040
|View full text |Cite
|
Sign up to set email alerts
|

LncRNA Sox2ot modulates the progression of thoracic aortic aneurysm by regulating miR-330-5p/Myh11

Abstract: Thoracic aortic aneurysm (TAA) has been causing the death of elder people. Myosin heavy chain 11 (Myh11) has been reported associated with aortic aneurysm, but there is no specific study on its function on TAA. Here we aimed to explore the function of Myh11 on mouse aortic smooth muscle cells (SMCs) for studying the inner mechanism of TAA. H2O2 treatment was implemented on mouse aortic SMCs for detecting cell apoptosis. Meanwhile, functional assays were conducted to verify the function of Myh11 on mouse aortic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…The mechanism of such phenomenon could be explained by the oligogenic model [19]. Markedly decreased cell apoptosis and increased proliferation were found in the aortic SMCs of Myh11 −/− mice [20], and the case with arterial stenosis in the intracranial vessel involvement caused by variants of MYH11 has been reported recently [21], indicating that there are other potential mechanisms of variants in MYH11 which remain to be explored. The mechanism by which variants in MYH11 result in TAAD/PDA is complex, and the genotype-phenotype correlation of MYH11 has not been clearly determined.…”
Section: Discussionmentioning
confidence: 94%
“…The mechanism of such phenomenon could be explained by the oligogenic model [19]. Markedly decreased cell apoptosis and increased proliferation were found in the aortic SMCs of Myh11 −/− mice [20], and the case with arterial stenosis in the intracranial vessel involvement caused by variants of MYH11 has been reported recently [21], indicating that there are other potential mechanisms of variants in MYH11 which remain to be explored. The mechanism by which variants in MYH11 result in TAAD/PDA is complex, and the genotype-phenotype correlation of MYH11 has not been clearly determined.…”
Section: Discussionmentioning
confidence: 94%
“…MYH11 gene is involved in vascular contractility and vascular wall stability ( 43 , 44 ). For instance, it can decrease the proliferation and enhance the apoptosis of SMCs ( 45 ). Numerous studies on MYH11 and thoracic AD have been reported, and it is found that the heterozygous mutations of MYH11 are more susceptible to AD ( 7 , 46 ).…”
Section: Discussionmentioning
confidence: 99%
“…Fbn1 C1041G/+ mice: This mouse model of Marfan syndrome represents the most commonly used genetic model in investigating TAA [40,52,[75][76][77][78][79][80][81][82][83][84][85][86][87]. Fbn1 C1041G/+ mice, also known as Fbn1 C1039G/+ mice, are generated by substitution of cysteine with glycine at amino acid 1041 (C1041G) in exon 25 of fibrillin-1 (previously identified in the literature as C1039G) [88].…”
Section: Genetic Taa Models In Rodentsmentioning
confidence: 99%